1997
DOI: 10.1097/00006123-199708000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Coagulative and Fibrinolytic Activation in Cerebrospinal Fluid and Plasma after Subarachnoid Hemorrhage

Abstract: Both the coagulative and fibrinolytic systems were activated in the CSF and plasma after SAH in correlating to the amount of SAH clot. The intrathecal administration of fibrinolytic agents should be started early after surgery, before CSF PAI-1 levels increase, for patients with severe SAH. Patients with CSF PAI-1 levels greater than 20 ng/ml experienced high incidence of VS and poor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…The levels of activated proteases in these systems reportedly elevate in the CSF during the acute phase after SAH, which is considered to be an etiologic factor of cerebral vasospasm. 10,[12][13][14]27 FUT-175 inhibits complement factors thrombin and plasmin and suppresses the protease-based inflammation. 18,19 FUT-175 has been used for disseminated intravascular coagulation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of activated proteases in these systems reportedly elevate in the CSF during the acute phase after SAH, which is considered to be an etiologic factor of cerebral vasospasm. 10,[12][13][14]27 FUT-175 inhibits complement factors thrombin and plasmin and suppresses the protease-based inflammation. 18,19 FUT-175 has been used for disseminated intravascular coagulation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…11) However, little data on tPA and plasminogen activator inhibitor-1 activities in CSF after SAH are available. 7,17) The hypothesis of the present investigation was that washout of extrinsic tPA does not depend on the initial dose, but on the individual patient conditions, such as anatomical variations of the cisterns, extent of surgical opening of the cistern walls, and J. Jito et al…”
Section: Introductionmentioning
confidence: 78%
“…Third, the plasminogen activator inhibitor-1 level is significantly high in the CSF and plasma of patients with severe SAH. 7) Therefore, a treatment strategy to remove clots effectively from the cisterns and ventricles requires adequate amounts of extrinsic thrombolytic factors to be given directly to the clots in the CSF space.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 was also the highest in the 120-IU/mL group, and it gradually decreased during the irrigation period. Ikeda et al 20 reported that patients whose PAI-1 levels in CSF were Ͼ20 ng/mL had a high incidence of vasospasm and a poor outcome. However, the fact that TAT and PAI-1 were highest in the 120-IU/mL group in the present study suggested that these results were due to clot lysis or clot volume.…”
Section: Discussionmentioning
confidence: 99%